Kerak Telor Makanan Khas DKI Jakarta - Fahrezzy Dwitama Adriansyah; Asep Parantika (Jurnal Ilmiah Wahana Pendidikan, 2023)
Jakarta is a big city known for its unique cultural cuisine. In Indonesia, delicacies such as kuerak telor are offered to customers regardless of their philosophical beliefs. This study aims to explore how a gastronomic and philosophical awareness of the origins of Kerrak Telor can help define the circumstances in which Betawi culinary preservation exists. Kerak Telor culinary centers in North and South Jakarta are located in Kemayoran and Setu Babakan. This data collection approach uses the method of observation, interviews, and recording. The data were then examined qualitatively and presented descriptively. With an emphasis on historical aspects and the origins of the naming of crust telor, food culture, geographic landscapes, as well as management and maintenance activities carried out by the DKI Jakarta government, this research uses a descriptive qualitative approach. Study location data is the result of empowerment carried out by the DKI Jakarta government. The way to carry out promotions is to take advantage of consumer tastes which have proven to be quite successful in promoting one of the cultural heritages of DKI Jakarta Province.